Lung stem cells: Do they exist?. Issue 4 (25th April 2013) - Bertoncello, Ivan; McQualter, Jonathan L.
Abstract Recognition of the potential of stem cell‐based therapies for alleviating intractable lung diseases has provided the impetus for research aimed at identifying regenerative cells in the adult lung, understanding how they are organized and regulated, and how they could be harnessed in lung regenerative medicine. In this review, we describe the attributes of adult stem and progenitor cells in adult organs and how they are regulated by the permissive or restrictive microenvironment in which they reside. We describe the power and limitations of experimental models, cell separative strategies and functional assays used to model the organization and regulation of adult airway and alveolar stem cells in the adult lung. The review summarizes recent progress and obstacles in defining endogenous lung epithelial stem and progenitor cells in mouse models and in translational studies.